The complete mitochondrial genome of spiny spooner Etisus dentatus (Herbst, 1785) using high-throughput sequencing - Hongtao Liu; MingHui Shen (Mitochondrial DNA. Part B. Resources, 2021)
The whole mitochondrial genome of the spiny spooner Etisus dentatus collected from the South China Sea was determined for the first time using high-throughput sequencing. The circular mitogenome of E. dentatus is 15,884 bp, with 13 protein-coding genes (PCGs), 22 tRNA genes, two rRNA genes. The base composition is significantly biased (A, G, T, and C was 37.9%, 17.8%, 34.0%, and 10.3%, respectively) with A + T contents of 71.9%. Among 13 PCGs, all PCGs use a normal ATN as the start codon, and ten of them end with TAA or TAG except COX1, COX2 and CYTB gene using a single T as the stop codon. The phylogenetic tree showed that E. dentatus forms a cluster E. anaglyptus while Atergatis integerrimus form a sister group to this cluster.